Advanced digital design with the Verilog HDL - Ciletti, Michael D. (Boston, Massachusetts : Pearson, 2011)
Advanced Digital Design with the Verilog HDL, 2e, is ideal for an advanced course in digital design for seniors and first-year graduate students in electrical engineering, computer engineering, and computer science. This book builds on the student's background from a first course in logic design and focuses on developing, verifying, and synthesizing designs of digital circuits. The Verilog language is introduced in an integrated, but selective manner, only as needed to support design examples (includes appendices for additional language details). It addresses the design of several important circuits used in computer systems, digital signal processing, image processing, and other applications.
1 Introduction to Digital Design Methodology -- 2 Review of Combinational Logic Design -- 3 Fundamentals of Sequential Logic Design -- 4 Introduction to Logic Design with Verilog -- 5 Logic Design with Behavioral Models of Combinational and Sequential Logic -- 6 Synthesis of Combinational and Sequential Logic -- 7 Design and Synthesis of Datapath Controllers -- 8 Programmable Logic and Storage Devices -- 9 Algorithms and Architectures for Digital Processors -- 10 Architectures for Arithmetic Processors
Includes index.
Keywords: LOGIC DESIGN -- DATA PROCESSING